Building energy efficiency in European cities. - Lewis, J. Owen; Ní Hógáin, Sadhbh; Borghi, Antonio (My University, 2013)
Cities can lead in the reduction of CO2 emissions and the fight against climate change. Buildings are the largest energy-consuming sector in the EU, and offer the largest cost-effective opportunity for savings. Relative to almost all other investments, energy efficiency retrofit installing newer energy efficiency technologies in older buildings cost-effectively creates more distributed jobs and enhances economic activity, reduces costs for businesses and households of all income levels, reduces emissions and improves energy security. However, considerable intensification in the delivery of ambitious whole-building energy efficiency upgrade programmes is needed. The gaps between consumers actual investments in energy efficiency and those that appear to be in the consumer s own interest demand new approaches to finance which incentivise energy efficiency upgrading. Far too many European households are living in fuel poverty; tackling this is not solely about saving money or reducing the impact of climate change, but has implications for health, child poverty, and educational achievement. As the European building stock is highly diverse, particularly in historic and traditional buildings, there are no one-size-fits-all solutions. Integrated urban strategies provide the means to tackle the various challenges faced by cities. These strategies must link together the social, environmental and economic policy dimensions, connect the various levels of responsible governance, and involve the key stakeholders in the implementation of an energy efficiency policy for each municipal building stock. The scale and extent of the radical changes required are not yet generally appreciated.
Keywords: Stadtentwicklungsplanung; Energie; Energiepolitik; Energieeinsparung; Alternativenergie; Erneuerbare Energie; Energieeffizienz; Nachhaltige Stadtentwicklung; Klimaschutz